Lysostaphin Cream Eradicates Staphylococcus aureus Nasal Colonization in a Cotton Rat Model - Kokai-Kun, John F. (American Society for Microbiology, 2003)
The anterior nares are a primary ecologic niche for Staphylococcus aureus, and nasal colonization by this opportunistic pathogen increases the risk of development of S. aureus infection. Clearance of S. aureus nasal colonization greatly reduces this risk. Mupirocin ointment is the current standard of care for clearance of S. aureus nasal colonization, but resistance to this antibiotic is emerging. Lysostaphin is a glycylglycine endopeptidase which specifically cleaves the cross-linking pentaglycine bridges in the cell walls of staphylococci. Lysostaphin is extremely staphylocidal (MIC at which 90% of isolates are inhibited, 0.001 to 0.064 μg/ml) and rapidly lyses both actively growing and quiescent S. aureus. This study demonstrates that a single application of 0.5% lysostaphin (actual dose, ∼150 μg of lysostaphin), formulated in a petrolatum-based cream, dramatically reduces S. aureus nasal colonization in 100% of animals tested and eradicates S. aureus nasal colonization in 93% of animals in a cotton rat model. A single dose of lysostaphin cream is more effective than a single dose of mupirocin ointment in eradicating S. aureus nasal colonization in this animal model. The lantibiotic peptide nisin, which has potent in vitro antistaphylococcal activity, was ineffective in reducing staphylococcal nasal carriage in this model. Nasal colonization was not reduced after three treatments with 5% nisin (∼1,500 μg/dose) in any of the treated animals. Lysostaphin formulated in cream may prove to be a superior alternative to mupirocin ointment for clearance of S. aureus nasal colonization.